2006
DOI: 10.5194/acp-6-2465-2006
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Condensation Nuclei properties of model and atmospheric HULIS

Abstract: Abstract. Humic like substances (HULIS) have been identified as a major fraction of the organic component of atmospheric aerosols. These large multifunctional compounds of both primary and secondary sources are surface active and water soluble. Hence, it is expected that they could affect activation of organic aerosols into cloud droplets. We have compared the activation of aerosols containing atmospheric HULIS extracted from fresh, aged and pollution particles to activation of size fractionated fulvic acid fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
216
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(233 citation statements)
references
References 101 publications
15
216
2
Order By: Relevance
“…HULIS exhibits strong surface activity that can influence the properties of the gaseliquid interface of droplets, and the multiphase or liquid phase water chemistry (Kiss et al, 2005;Dinar et al, 2006). Consequently, HULIS can influence the surface tension and growth of nucleating cloud droplets, and thereby would have important impacts on the cloud microphysical properties, the indirect climatic forcing of atmospheric aerosol (Kiss et al, 2005;Dinar et al, 2006;Fuzzi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HULIS exhibits strong surface activity that can influence the properties of the gaseliquid interface of droplets, and the multiphase or liquid phase water chemistry (Kiss et al, 2005;Dinar et al, 2006). Consequently, HULIS can influence the surface tension and growth of nucleating cloud droplets, and thereby would have important impacts on the cloud microphysical properties, the indirect climatic forcing of atmospheric aerosol (Kiss et al, 2005;Dinar et al, 2006;Fuzzi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…HULIS are present ubiquitously in the atmospheric environments, and their carbon content makes up a mass fraction up to about 60% of the water soluble organic carbon (WSOC) in ambient aerosols (Krivácsy et al, , 2008Salma et al, 2007;Lin et al, 2010). HULIS exhibits strong surface activity that can influence the properties of the gaseliquid interface of droplets, and the multiphase or liquid phase water chemistry (Kiss et al, 2005;Dinar et al, 2006). Consequently, HULIS can influence the surface tension and growth of nucleating cloud droplets, and thereby would have important impacts on the cloud microphysical properties, the indirect climatic forcing of atmospheric aerosol (Kiss et al, 2005;Dinar et al, 2006;Fuzzi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment of air particles in WSOC and its mixing state with the inorganic counterpart plays an important role in several atmospheric processes. The WSOC might potentially affect the properties that determine the aerosols' ability to act as cloud condensation nuclei (Dinar et al, 2006;Padro et al, 2010). It has been also suggested that the WSOC might contribute to the absorption of solar radiation, and thus atmospheric heating and global climate change (Dinar et al, 2008;Mladenov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As yet, these isolation and characterization approaches have not been applied to dust, although hulis and BC in aerosol have been widely studied in the past (Havers et al, 1998;Krivácsy et al, 2000;Dinar et al, 2006;Taraniuk et al, 2007;Kirchstetter et al, 2008;Dutkiewicz et al, 2009;Sýkorová et al, 2009). In the present study, we isolated HAs, kerogen and black carbon (KB) and BC from dust collected in Guangzhou, China, and then characterized the chemical composition of the fractionated macromolecule organic matter using elementary analysis (EA), X-ray diffraction (XRD), organic petrographic examination (OPE), scanning electron microscopy (SEM), solid state 13 C cross-polarization and magic angle spinning nuclear magnetic resonance spectroscopy ( 13 C-CP/MAS NMR) and Fourier transformed infrared spectroscopy (FTIR).…”
Section: Introductionmentioning
confidence: 99%